IC 6626 Method And Cost Of Dredging Sand And Gravel, Portland Gravel Co., Portland, Oregon ? Introduction - Howard F. Puariea (The National Institute for Occupational Safety and Health (NIOSH), 1932)
This paper is one of a series describing methods and costs of recovering sand and gravel from alluvial deposits in the United States and deals directly with the methods employed by the Portland Gravel Co. in operating a clamshell dredge on the Willamette River near Portland, Oreg., and a pump dredge on the Columbia River near Vancouver, Wash. These papers are designed to disseminate technical information regarding the methods used. The cost tabulations represent local expenditures only and not total production costs. It is recognized that publication of total costs may in some instances cause embarrassment to individual producers as well as to the industry as a whole. On the other hand operating costs are essential to the technical discussion and study of methods employed. The attention of the reader is specifically called to this differentiation in order that no misunderstanding of the scope of the cost tabulations shall ensue.